Особенности торможения капель огнетушащей жидкости в пламени; Пожарная безопасность; № 3 - Волков Р. С. Роман Сергеевич; Забелин М. В. Максим Валерьевич; Кузнецов Г. В. Гений Владимирович; Стрижак П. А. Павел Александрович; Хасанов И. Р. Ирек Равильевич (2015, 2015)
Заглавие с экрана